2021
DOI: 10.5696/2156-9614-11.31.210903
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Exposure to Polycyclic Aromatic Hydrocarbons and Obstructive Lung Disease

Abstract: Background. There is fast-growing epidemiologic evidence of the effects of environmental chemicals on respiratory health. Polycyclic aromatic hydrocarbons (PAHs) have been linked with airway obstruction common in asthma and/or asthma exacerbation, and chronic bronchitis and emphysema. Objectives. A systematic review of the association between exposure to PAHs and obstructive lung diseases is not yet available. The present sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 58 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Recent studies carried out in Romania showed different concentrations of PAHs in serum for donors from the urban and rural areas, especially for the N, Fl, P, and Py [ 14 ]. Many epidemiological studies involving a large number of participants have observed that compounds with 2–4 benzenic rings, such as N, P, Fl, and Py, as well as compounds with more than four benzenic rings, were associated with obstructive lung diseases [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies carried out in Romania showed different concentrations of PAHs in serum for donors from the urban and rural areas, especially for the N, Fl, P, and Py [ 14 ]. Many epidemiological studies involving a large number of participants have observed that compounds with 2–4 benzenic rings, such as N, P, Fl, and Py, as well as compounds with more than four benzenic rings, were associated with obstructive lung diseases [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some chemical exposures, such as polyaromatic hydrocarbons, phthalates, and pesticides, have been shown to be associated with poor respiratory outcomes, there is less robust data on others, including volatile organic compounds and polybrominated diphenyl ethers ( 9 12 ).…”
Section: Environmental Triggers Of Copd Exacerbationsmentioning
confidence: 99%